Historia Compostelana: Acerca de su toponimia - Martínez Ortega, Ricardo (1998)
The «Historia compostellana» (XIIth century), a famous Spanish medieval literary work, contains several place name references which have either not yet been identified or the locations of which are in doubt. The aim of this article is to identify and specifically locate a dozen or so of these place names, amongst which we find «Orzelione» and «Sª Mª de Octaris», places about which there has been special discussion. The author used his own methods in conducting this research, which combined the extrinsic comparison of the place names together with the intrinsic study of the related documents.
Keywords: Historia Compostelana; Toponimia